(untitled) (Modern education and development, 2024)
This study explores the potential of blended learning models in enhancing language learning by integrating interactive digital tools and multimedia resources. Preliminary results indicate a strong correlation between technology use and language proficiency gains, with a significant number of respondents expressing satisfaction with digital tools. However, the variability in results emphasises the need for individualised approaches that take into account different learner preferences. In investigating best practices for implementing blended learning, this study aims to provide valuable information for educators seeking to optimise language acquisition in a rapidly changing educational landscape.